Treatment-refractory heart failure as a manifestation of aortic arch atresia - Luis A. González-Ramos; Erika M. Martínez-Carballo; Jesús E. Anaya-García; Jessica Sánchez-Cárdenas; Kenya N. Velázquez-Fontes; Daniel Mazariego-Pedraza (Permanyer, 2022)
Background: Distal segment atresia (isthmus) is an extremely rare anatomical variant of obstructive aortic arch anomalies. Case report: We present the case of a newborn who, at 48 hours of life, presented a clinical picture of heart failure. The initial echocardiogram showed a congenital interrupted aortic arch type A, patent ductus arteriosus, and ventricular septal defect. Prostaglandins were initially indicated. Subsequently, a second echocardiogram showed the absence of ductus arteriosus; the CT angiography study confirmed this finding and revealed blood flow to the descending aorta through small intercostal blood vessels. The possibility of atresia of the distal segment (isthmus) of the aortic arch was considered and confirmed at the time of surgery. Conclusions: Aortic atresia should be considered a diagnostic possibility in the presence of type A interrupted aortic arch since the hemodynamic behavior between them is similar. Surgical medical treatment should be individualized since this condition is frequently an emergency in the neonatal period. However, this is not always the case, as other cases have been reported in schoolchildren and adults.